2007
DOI: 10.1300/j457v03n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Planning and Decision-Making Among Midlife and Older Gay Men and Lesbians

Abstract: This article examines the issues of long-term planning and decision-making among midlife and older gay men and lesbian caregivers. Using a qualitative methodology, in-depth interviews were conducted with 19 gay men and lesbians over 50. Participants reported on their long-term planning and decision-making processes. All but four persons reported that their partners had advance directives, but the majority of caregivers did not have advance directives for themselves. Concerns about informal family dynamics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…The findings of this study, like those in international research (Auger 2003;Hash and Netting 2007;Smolinski and Colón 2006;Stein and Bonuck 2001), highlight the need for GLBT people to engage in advance care planning because of the discrimination they may face in health care settings and the lack of understanding of the complexity and significance of GLBT people's 'families of choice'. When advance care planning takes place, it can mitigate discrimination.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The findings of this study, like those in international research (Auger 2003;Hash and Netting 2007;Smolinski and Colón 2006;Stein and Bonuck 2001), highlight the need for GLBT people to engage in advance care planning because of the discrimination they may face in health care settings and the lack of understanding of the complexity and significance of GLBT people's 'families of choice'. When advance care planning takes place, it can mitigate discrimination.…”
Section: Discussionsupporting
confidence: 52%
“…Advance care planning can protect some rights at the end of life but, like the rest of the population, GLBT people need to use the legal mechanisms available and service providers need to promote their use (Auger 2003;Hash and Netting 2007;Stein and Bonuck 2001).…”
Section: Glbt People's Experiences With End-of-life Care and Advance mentioning
confidence: 99%
“…Hughes' (2009) analysis of a survey of 372 lesbian and gay people in relation to aging found that 46% of the participants expected discrimination in aged care because of their sexuality. Similar findings have been reported by other studies (Hash & Netting, 2007;Johnson, Jackson, Arnette & Koffman, 2005;Metlife, 2010). Older LGBTI people have been seen as reluctant to engage with the health care system for fear of discrimination (Almack, Seymour & Bellamy, 2010) and studies have shown that for the most part older LGBTI people are cared for in their own homes by other LGBTI people, or what is often described as "family of choice" (Cohen, Curry, Jenkins, Walker, Hogstel, 2008;Hash, 2008;Neville & Henrickson, 2010).…”
Section: Please Scroll Down For Articlesupporting
confidence: 93%
“…Terms & 2010). This has in part been put down to the heteronormative nature of health care, a lack of recognition of older people's sexual lives, and a fear on the part of older LGBTI people of discrimination and abuse from the health care system in general (Callan & Mitchell, 2007;Cronin, Ward, Pugh, King & Price, 2011;Hash & Netting, 2007;Hughes & Kentlyn, 2011). Many of the older LGBTI people entering end-of-life care today carry with them the scars of discrimination of their generation (Lee & Quam, 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…With regards to financial resources in the United States, same sex partners do not have automatic next-of-kin status for hospital visits and medical decision-making, nor do they have family leave benefits, bereavement leave or automatic inheritance of jointly-owned real estate and personal property (Hash & Netting, 2007). According to Pierre de Vos, Constitutional Law expert and lecturer at UCT (telephonic interview on the 26 th of August, 2015), there is automatic next-of kin status for same-sex partners in South Africa, which includes all the benefits noted above.…”
Section: Legal Ramifications For Older Lgbt People Within Eolcmentioning
confidence: 99%